Bioinformatic and image analyses of the cellular localization of the apoptotic proteins endonuclease G, AIF, and AMID during apoptosis in human cells - Varecha, Miroslav; Amrichová, Jana; Zimmermann, Michal; Ulman, Vladimír; Lukásová, Emilie; Kozubek, Michal (Apoptosis, 2007)
We studied the cellular localization of the apoptotic proteins endonuclease G, AIF, and AMID in silico using three prediction tools and in living cells using both single-cell colocalization image analysis and nuclear translocation analysis. We confirmed the mitochondrial localization of endonuclease G and AIF by prediction analysis and by single-cell colocalization image analysis. We found the AMID protein to be cytoplasmic, most probably incorporated into the cytoplasmic side of the membranes of various organelles. The highest concentration of AMID was observed associated with the Golgi. Colocalization of AMID with lysosomes was also indirectly confirmed by analysis of AMID-rich vesicle velocity using manual tracking analysis. Bioinformatic analysis also detected nuclear localization signals in endonuclease G and AIF, but not in AMID. A novel analysis of time-lapse fluorescence image data during staurosporine-induced apoptosis revealed nuclear translocation only for endonuclease G and AIF.
Keywords: intracelulární membrány; faktor vyvolávající apoptózu; Intracellular Membranes; Golgiho aparát; apoptóza; Lysosomes; buněčné linie; Microscopy, Fluorescence; Mitochondria; lyzozomy; Apoptosis; Recombinant Fusion Proteins; endodeoxyribonukleasy; rekombinantní fúzní proteiny; lidé; Cell Nucleus; Golgi Apparatus; mitochondriální proteiny; fluorescenční mikroskopie; Cell Line; Endodeoxyribonucleases; mitochondrie; buněčné jádro; Computational Biology; Apoptosis Regulatory Proteins; proteiny regulující apoptózu; Mitochondrial Proteins; výpočetní biologie; Apoptosis Inducing Factor; Humans